Composite coating tool and preparation method thereof

By using physical vapor deposition method to prepare composite coatings, including multi-layer structure coatings, the serious wear of cemented carbide tools in high-speed cutting is solved, and high bond strength, wear resistance and Oxidation resistance, extends tool life and improves cutting performance.

CN118880239BActive Publication Date: 2024-12-13GANZHOU ACHTECK TOOL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411382969.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing cemented carbide tools have severe wear during high-speed cutting, which affects the surface quality of the processed parts. It is difficult for existing coating technology to improve wear resistance, oxidation resistance and bonding strength at the same time.

Method used

The composite coating was prepared by physical vapor deposition method, including M bonding layer, MN transition layer, Al1-xTixN intermediate layer, NbaAlbBcSidN functional layer and ZrN surface layer, and high binding strength, wear resistance and oxidation resistance are achieved through arc ion plating technology. sex.

Benefits of technology

It improves the service life and cutting performance of the tool, enhances the hardness and anti-viscosity of the coating, simplifies the preparation process, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118880239B_ABST
    Figure CN118880239B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of mechanical processing tools, and specifically relates to a composite coating tool and a preparation method thereof. The composite coating tool prepared by arc ion plating process comprises a cemented carbide tool substrate and a composite coating on the substrate. 1‑x Ti x As an intermediate layer, the N coating has high bonding strength, thereby improving the Nb a Al b B c Si d The bonding strength between the N functional layer and the substrate; due to the Nb a Al b B c Si d a‑Si3N4 and BN in the N coating work together to refine the grains, and a‑Si3N4 and BN have excellent resistance to chemical diffusion; and ZrN is used as the surface layer, so the composite coated tool not only has high hardness and high bonding strength, but also has good oxidation resistance and anti-stickiness; and the preparation process of the composite coated tool is simple, easy to operate, and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mechanical processing tools, and specifically relates to a composite coating tool and a preparation method thereof. Background Art

[0002] In the field of mechanical processing, carbide tools play an important role in cutting various materials. During the processing, as the processing time increases, tool wear or tool sticking will occur. Especially in high-speed cutting, tool wear is extremely serious, and wear also affects the surface quality of the workpiece. In order to increase the life of the tool and for today's various difficult-to-process materials, the wear resistance and oxidation resistance of the coating must be improved as soon as possible, and the coating's anti-stickiness and bonding strength also need to be improved.

[0003] The surface coating technology of cutting tools is a hot topic that researchers have been paying close attention to. The use of coating technology can make the tool have higher hardness, good oxidation resistance and wear resistance, thereby increasing the service life of the tool. In the prior art, AlNbN coatings have been studied. After heat treatment at 1000°C, the coating still maintains its mechanical properties unchanged, showing excellent high temperature stability, but its hardness is relatively low. In the prior art, Si elements are also added to TiN to form TiSiN, which has superior coating performance, and the content of Si elements has a significant effect on TiSiN coatings; it is not only related to the microstructure and mechanical response of the material, but also to the strength and tribological properties of the material. Prior art research shows that B added to AlCrN coatings significantly improves its coating performance. The reason is that amorphous BN can inhibit the growth of AlCrN grain size, thereby improving the oxidation resistance and wear resistance of the coating. However, due to its large internal stress, the film-base bonding strength is poor, which limits its application. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the main purpose of the present invention is to provide a composite coating tool and a preparation method thereof, which has excellent wear resistance, anti-stickiness and film-base bonding strength, and also has good oxidation resistance.

[0005] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:

[0006] A composite coating tool, characterized by comprising a cemented carbide tool substrate and a composite coating on the substrate;

[0007] The composite coating is prepared by a physical vapor deposition method, and includes, from the substrate to the outside, an M bonding layer, an MN transition layer deposited on the surface of the M bonding layer, an Al 1-x Ti x N intermediate layer, deposited on Al1-x Ti x Nb on the surface of N intermediate layer a Al b B c Si d N functional layer, deposited on Nb a Al b B c Si d ZrN coating on the surface of N functional layer;

[0008] Among them, 0.4≤x≤0.6, 0<a≤0.6, 0<b≤0.4, 0<c≤0.08, 0<d≤0.08, a+b+c+d=1.

[0009] As a preferred embodiment of the composite coating tool described in the present invention, the thickness of the M bonding layer is 0.05-0.1 μm; the M bonding layer is any one of a Nb bonding layer, a Zr bonding layer and a Ta bonding layer.

[0010] As a preferred embodiment of the composite coating tool described in the present invention, the thickness of the MN transition layer is 0.1-0.2 μm; the MN transition layer is any one of a NbN transition layer, a ZrN transition layer and a TaN transition layer.

[0011] As a preferred embodiment of the composite coating tool described in the present invention, wherein: the Al 1-x Ti x The thickness of the N intermediate layer is 0.1~0.5μm and the hardness is 22~26GPa.

[0012] As a preferred embodiment of the composite coating tool described in the present invention, wherein: the Nb a Al b B c Si d The thickness of the N functional layer is 0.5~3.5μm, the hardness is 30~43GPa, the friction coefficient is 0.3~0.5, and the Nb a Al b B c Si d In the N functional layer, amorphous BN and amorphous Si3N4 cover Al(Nb)N nanocrystals, the volume fraction of the amorphous phase is 5-20%, and the volume fraction of amorphous Si3N4 is greater than that of amorphous BN. The size of the Al(Nb)N nanocrystals is 2-100nm.

[0013] As a preferred embodiment of the composite coating tool described in the present invention, the ZrN coating has a thickness of 0.2-0.7 μm and a hardness of 20-30 GPa.

[0014] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:

[0015] A method for preparing a composite coating tool, wherein the composite coating is prepared by an arc ion plating process, comprising the following steps:

[0016] S1, depositing a bonding layer M on the substrate;

[0017] S2, depositing a MN transition layer on the surface of the M bonding layer;

[0018] S3, Al deposition on the surface of MN transition layer 1-x Ti x N intermediate layer; deposition process parameters are:

[0019] The temperature is 400~550℃, the bias voltage is -80~-120V, the arc current is 100~130A, and the gas pressure is 5.0×10 -2 ~1.0×10 -1 mbar, N2 flow rate is 1000~2500sccm, and time is 8~40min;

[0020] S4. In Al 1-x Ti x Nb is deposited on the surface of N intermediate layer a Al b B c Si d N functional layer; deposition process parameters are:

[0021] The temperature is 400~550℃, the bias voltage is -60~-120V, the arc current is 100~140A, and the gas pressure is 5.0×10 -2 ~1.0×10 -1 mbar, N2 flow rate is 1000~2500sccm, and time is 40~280min;

[0022] S5, in Nb a Al b B c Si d ZrN coating is deposited on the surface of N functional layer; the deposition process parameters are:

[0023] The temperature is 400~550℃, the bias voltage is -40~-100V, the arc current is 100~140A, and the gas pressure is 5.0×10 -2 ~1.0×10 -1 mbar, N2 flow rate is 1000~2500sccm, and time is 16~56min;

[0024] S6. After the temperature drops to room temperature, take out the sample at room temperature to obtain a composite coating tool.

[0025] As a preferred embodiment of the method for preparing a composite coating tool according to the present invention, the method further comprises:

[0026] S0. Pre-processing;

[0027] The carbide tool is used as a substrate. After being sandblasted, cleaned and dried, the substrate is placed on a rotating rack, and the surface of the substrate is cleaned by glow discharge.

[0028] As a preferred embodiment of the method for preparing a composite coating tool according to the present invention, in step S1, the specific process parameters for depositing the M bonding layer on the substrate are:

[0029] The temperature is 400~550℃, the bias voltage is -120~-200V, the arc current is 100~140A, and the gas pressure is 0.8×10 -2 ~2.0×10 -2 mbar, Ar flow rate is 1000~2000sccm, and time is 4~8min.

[0030] As a preferred embodiment of the method for preparing a composite coating tool according to the present invention, the specific process parameters for depositing the MN transition layer on the surface of the M bonding layer in step S2 are:

[0031] The temperature is 400~550℃, the bias voltage is -80~-150V, the arc current is 100~140A, and the gas pressure is 5.0×10 -2 ~1.0×10 -1 mbar, N2 flow rate is 1000~2500sccm, and time is 8~16min.

[0032] The beneficial effects of the present invention are as follows:

[0033] The present invention provides a composite coating tool and a preparation method thereof. The composite coating tool prepared by arc ion plating process comprises a cemented carbide tool substrate and a composite coating on the substrate. 1-x Ti x As an intermediate layer, the N coating has high bonding strength, thereby improving the Nb a Al b B c Si d The bonding strength between the N functional layer and the substrate; due to the Nb a Al b B c Si da-Si3N4 and BN in the N coating work together to refine the grains, and a-Si3N4 and BN have excellent resistance to chemical diffusion; and ZrN serves as the surface layer, so the composite coated tool not only has high hardness and high bonding strength, but also has good oxidation resistance and anti-stickiness; and the preparation process of the composite coated tool is simple, easy to operate, and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0035] Figure 1 It is a schematic cross-sectional view of the composite coating tool of the present invention.

[0036] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0037] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The present invention provides a composite coating tool and a preparation method thereof, which has the following advantages:

[0039] (1) The present invention provides a composite coating tool and a method for preparing the same. The cross-sectional schematic diagram of the composite coating tool is as follows: Figure 1 As shown in the figure, according to the changes in coating composition, it is divided into: bonding layer, transition layer, intermediate layer, functional layer, and surface layer; the MN transition layer is deposited on the surface of the M bonding layer, which has a very strong bonding strength with the substrate; Al 1-x Ti x As the middle layer, N coating not only has good oxidation resistance, but also its face-centered structure can improve the bonding strength between membranes; Nb a Al b B c Si dThe N coating is a functional layer with excellent wear resistance, toughness and oxidation resistance; at the same time, the surface layer is a ZrN coating, which has excellent chemical stability and is not prone to oxidation or other chemical reactions on the surface, and can play an anti-sticking role to prevent the knife from sticking; therefore, the composite coating finally obtains excellent bonding strength, wear resistance, oxidation resistance and adhesion resistance;

[0040] 2. Preparation of Al 1-x Ti x N / Nb a Al b B c Si d N / ZrN composite coating, adding Si element to AlNbN coating can significantly improve the hardness of the coating; because Si element can easily combine with N element to form amorphous Si3N4, and amorphous Si3N4 cannot form solid solution with NbAlN grains, and can only exist in the crystal plane in the form of interface phase; therefore, the constraint on the grains is increased to inhibit their growth, so it is difficult for fine grains to produce dislocation proliferation under the action of external force, thereby improving the hardness; in addition, the presence of amorphous phase can also effectively improve the resistance to grain boundary sliding, and improve toughness by blocking the extension of microcracks; at the same time, adding B element will also produce amorphous BN, and the two amorphous states have a synergistic effect on the grains, with better coating performance; therefore, the composite coating has a longer service life.

[0041] According to one aspect of the present invention, the present invention provides the following technical solution:

[0042] A composite coating tool, characterized by comprising a cemented carbide tool substrate and a composite coating on the substrate;

[0043] The composite coating is prepared by physical vapor deposition method and has a thickness of 1 to 5 μm. From the substrate to the outside, it includes an M bonding layer, an MN transition layer deposited on the surface of the M bonding layer, an Al 1-x Ti x N intermediate layer, deposited on Al 1-x Ti x Nb on the surface of N intermediate layer a Al b B c Si d N functional layer, deposited on Nb a Al b B c Si d ZrN coating on the surface of N functional layer;

[0044] Among them, 0.4≤x≤0.6, 0<a≤0.6, 0<b≤0.4, 0<c≤0.08, 0<d≤0.08, a+b+c+d=1.

[0045] Preferably, the thickness of the M bonding layer is 0.05-0.1 μm; the M bonding layer is any one of a Nb bonding layer, a Zr bonding layer and a Ta bonding layer.

[0046] Preferably, the thickness of the MN transition layer is 0.1-0.2 μm; the MN transition layer is any one of a NbN transition layer, a ZrN transition layer and a TaN transition layer.

[0047] Preferably, the Al 1-x Ti x The thickness of the N intermediate layer is 0.1-0.5 μm, and the hardness is 22-26 GPa; specifically, x can be, for example but not limited to, any one of 0.4, 0.5, 0.6, or a range between any two;

[0048] Preferably, the Nb a Al b B c Si d The thickness of the N functional layer is 0.5~3.5μm, the hardness is 30~43GPa, the friction coefficient is 0.3~0.5, and the Nb a Al b B c Si d In the N functional layer, amorphous BN and amorphous Si3N4 cover Al(Nb)N nanocrystals, the volume fraction of the amorphous phase is 5-20%, and the volume fraction of amorphous Si3N4 is greater than the volume fraction of amorphous BN, and the size of the Al(Nb)N nanocrystals is 2-100 nm; specifically, a can be, for example but not limited to, any one of 0.01, 0.02, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 or a range between any two of them; b can be, for example but not limited to, 0.01 , 0.02, 0.05, 0.1, 0.2, 0.3, 0.4, or a range between any two of them; c can be, for example, but not limited to, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, or a range between any two of them; d can be, for example, but not limited to, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, or a range between any two of them.

[0049] According to another aspect of the present invention, the present invention provides the following technical solution:

[0050] A method for preparing a composite coating tool, wherein the composite coating is prepared by an arc ion plating process, comprising the following steps:

[0051] S1, depositing a bonding layer M on the substrate;

[0052] S2, depositing a MN transition layer on the surface of the M bonding layer;

[0053] S3, Al deposition on the surface of MN transition layer 1-x Ti x N intermediate layer; deposition process parameters are:

[0054] The temperature is 400~550℃, the bias voltage is -80~-120V, the arc current is 100~130A, and the gas pressure is 5.0×10 -2 ~1.0×10 -1 mbar, N2 flow rate is 1000~2500sccm, and time is 8~40min;

[0055] S4. In Al 1-x Ti x Nb is deposited on the surface of N intermediate layer a Al b B c Si d N functional layer; deposition process parameters are:

[0056] The temperature is 400~550℃, the bias voltage is -60~-120V, the arc current is 100~140A, and the gas pressure is 5.0×10 -2 ~1.0×10 -1 mbar, N2 flow rate is 1000~2500sccm, and time is 40~280min;

[0057] S5, in Nb a Al b B c Si d ZrN coating is deposited on the surface of N functional layer; the deposition process parameters are:

[0058] The temperature is 400~550℃, the bias voltage is -40~-100V, the arc current is 100~140A, and the gas pressure is 5.0×10 -2 ~1.0×10 -1 mbar, N2 flow rate is 1000~2500sccm, and time is 16~56min;

[0059] S6. After the temperature drops to room temperature, take out the sample at room temperature to obtain a composite coating tool.

[0060] Preferably, before step S1, the step further includes:

[0061] S0. Pre-processing;

[0062] The carbide tool is used as a substrate. After being sandblasted, cleaned and dried, the substrate is placed on a rotating rack, and the surface of the substrate is cleaned by glow discharge.

[0063] Preferably, in step S1, the specific process parameters for depositing the M bonding layer on the substrate are:

[0064] The temperature is 400~550℃, the bias voltage is -120~-200V, the arc current is 100~140A, and the gas pressure is 0.8×10 -2 ~2.0×10 -2 mbar, Ar flow rate is 1000~2000sccm, and time is 4~8min.

[0065] Preferably, in step S2, the specific process parameters for depositing the MN transition layer on the surface of the M bonding layer are:

[0066] The temperature is 400~550℃, the bias voltage is -80~-150V, the arc current is 100~140A, and the gas pressure is 5.0×10 -2 ~1.0×10 -1 mbar, N2 flow rate is 1000~2500sccm, and time is 8~16min.

[0067] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0068] Example 1

[0069] A method for preparing a composite coating tool, wherein the composite coating is prepared by an arc ion plating process, comprising the following steps:

[0070] S0 pre-treatment; carbide tool as the substrate, the substrate after sandblasting and cleaning and drying into the turntable, the substrate surface glow discharge cleaning;

[0071] S1. Turn on the Zr target and deposit a Zr bonding layer on the substrate with a thickness of 0.05 μm. The specific process parameters are:

[0072] The temperature is 450°C, the bias voltage is -150V, the arc current is 120A, and the gas pressure is 0.9×10 -2 mbar, Ar flow rate of 1200sccm, and time of 4min;

[0073] S2. Deposit a ZrN transition layer on the surface of the Zr bonding layer with a thickness of 0.1 μm. The specific process parameters are:

[0074] The temperature is 450°C, the bias voltage is -120V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 8min;

[0075] S3, turn off the Zr target and turn on the Al 0.55 Ti0.45 Target, deposit Al on the surface of ZrN transition layer 0.55 Ti 0.45 N transition layer, thickness is 0.2μm; deposition process parameters are:

[0076] The temperature is 450°C, the bias voltage is -100V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 16min;

[0077] S4. Close Al 0.55 Ti 0.45 Target, turn on Nb 0.5 Al 0.4 B 0.08 Si 0.02 Target, in Al 0.55 Ti 0.45 Nb is deposited on the surface of N transition layer 0.5 Al 0.4 B 0.08 Si 0.02 N functional layer, thickness is 3.0μm; deposition process parameters are:

[0078] The temperature is 450°C, the bias voltage is -80V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 240min;

[0079] S5. Close Nb 0.5 Al 0.4 B 0.08 Si 0.02 Target, open the Zr target, in Nb 0.5 Al 0.4 B 0.08 Si 0.02 A ZrN coating with a thickness of 0.2 μm is deposited on the surface of the N functional layer; the deposition process parameters are:

[0080] The temperature is 450°C, the bias voltage is -60V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 16min;

[0081] S6. After the temperature drops to room temperature, take out the sample to obtain a composite coated tool.

[0082] Example 2

[0083] A method for preparing a composite coating tool, wherein the composite coating is prepared by an arc ion plating process, comprising the following steps:

[0084] S0 pre-treatment; carbide tool as the substrate, the substrate after sandblasting and cleaning and drying into the turntable, the substrate surface glow discharge cleaning;

[0085] S1. Turn on the Zr target and deposit a Zr bonding layer on the substrate with a thickness of 0.05 μm. The specific process parameters are:

[0086] The temperature is 450°C, the bias voltage is -150V, the arc current is 120A, and the gas pressure is 0.9×10 -2 mbar, Ar flow rate of 1200sccm, and time of 4min;

[0087] S2. Deposit a ZrN transition layer on the surface of the Zr bonding layer with a thickness of 0.1 μm. The specific process parameters are:

[0088] The temperature is 450°C, the bias voltage is -120V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 8min;

[0089] S3, turn off the Zr target and turn on the Al 0.55 Ti 0.45 Target, deposit Al on the surface of ZrN transition layer 0.55 Ti 0.45 N transition layer, thickness is 0.2μm; deposition process parameters are:

[0090] The temperature is 450°C, the bias voltage is -100V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 16min;

[0091] S4. Close Al 0.55 Ti 0.45 Target, turn on Nb 0.5 Al 0.4 B 0.06 Si 0.04 Target, in Al 0.55 Ti 0.45 Nb is deposited on the surface of N transition layer 0.5 Al 0.4 B 0.06 Si 0.04 N functional layer, thickness is 3.0μm; deposition process parameters are:

[0092] The temperature is 450°C, the bias voltage is -80V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 240min;

[0093] S5. Close Nb0.5 Al 0.4 B 0.06 Si 0.04 Target, open the Zr target, in Nb 0.5 Al 0.4 B 0.06 Si 0.04 A ZrN coating with a thickness of 0.2 μm is deposited on the surface of the N functional layer; the deposition process parameters are:

[0094] The temperature is 450°C, the bias voltage is -60V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 16min;

[0095] S6. After the temperature drops to room temperature, take out the sample to obtain a composite coated tool.

[0096] Example 3

[0097] A method for preparing a composite coating tool, wherein the composite coating is prepared by an arc ion plating process, comprising the following steps:

[0098] S0 pre-treatment; carbide tool as the substrate, the substrate after sandblasting and cleaning and drying into the turntable, the substrate surface glow discharge cleaning;

[0099] S1. Turn on the Zr target and deposit a Zr bonding layer on the substrate with a thickness of 0.05 μm. The specific process parameters are:

[0100] The temperature is 450°C, the bias voltage is -150V, the arc current is 120A, and the gas pressure is 0.9×10 -2 mbar, Ar flow rate of 1200sccm, and time of 4min;

[0101] S2. Deposit a ZrN transition layer on the surface of the Zr bonding layer with a thickness of 0.1 μm. The specific process parameters are:

[0102] The temperature is 450°C, the bias voltage is -120V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 8min;

[0103] S3, turn off the Zr target and turn on the Al 0.55 Ti 0.45 Target, deposit Al on the surface of ZrN transition layer 0.55 Ti 0.45 N transition layer, thickness is 0.2μm; deposition process parameters are:

[0104] The temperature is 450°C, the bias voltage is -100V, the arc current is 120A, and the gas pressure is 6.2×10-2 mbar, N2 flow rate of 1500sccm, time of 16min;

[0105] S4. Close Al 0.55 Ti 0.45 Target, turn on Nb 0.5 Al 0.4 B 0.04 Si 0.06 Target, in Al 0.55 Ti 0.45 Nb is deposited on the surface of N transition layer 0.5 Al 0.4 B 0.04 Si 0.06 N functional layer, thickness is 3.0μm; deposition process parameters are:

[0106] The temperature is 450°C, the bias voltage is -80V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 240min;

[0107] S5. Close Nb 0.5 Al 0.4 B 0.04 Si 0.06 Target, open the Zr target, in Nb 0.5 Al 0.4 B 0.04 Si 0.06 A ZrN coating with a thickness of 0.2 μm is deposited on the surface of the N functional layer; the deposition process parameters are:

[0108] The temperature is 450°C, the bias voltage is -60V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 16min;

[0109] S6. After the temperature drops to room temperature, take out the sample to obtain a composite coated tool.

[0110] Example 4

[0111] A method for preparing a composite coating tool, wherein the composite coating is prepared by an arc ion plating process, comprising the following steps:

[0112] S0 pre-treatment; carbide tool as the substrate, the substrate after sandblasting and cleaning and drying into the turntable, the substrate surface glow discharge cleaning;

[0113] S1. Turn on the Zr target and deposit a Zr bonding layer on the substrate with a thickness of 0.05 μm. The specific process parameters are:

[0114] The temperature is 450°C, the bias voltage is -150V, the arc current is 120A, and the gas pressure is 0.9×10 -2 mbar, Ar flow rate of 1200sccm, and time of 4min;

[0115] S2. Deposit a ZrN transition layer on the surface of the Zr bonding layer with a thickness of 0.1 μm. The specific process parameters are:

[0116] The temperature is 450°C, the bias voltage is -120V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 8min;

[0117] S3, turn off the Zr target and turn on the Al 0.55 Ti 0.45 Target, deposit Al on the surface of ZrN transition layer 0.55 Ti 0.45 N transition layer, thickness is 0.2μm; deposition process parameters are:

[0118] The temperature is 450°C, the bias voltage is -100V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 16min;

[0119] S4. Close Al 0.55 Ti 0.45 Target, turn on Nb 0.5 Al 0.4 B 0.02 Si 0.08 Target, in Al 0.55 Ti 0.45 Nb is deposited on the surface of N transition layer 0.5 Al 0.4 B 0.02 Si 0.08 N functional layer, thickness is 3.0μm; deposition process parameters are:

[0120] The temperature is 450°C, the bias voltage is -80V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 240min;

[0121] S5. Close Nb 0.5 Al 0.4 B 0.02 Si 0.08 Target, open the Zr target, in Nb 0.5 Al 0.4 B 0.02 Si 0.08A ZrN lubricating layer with a thickness of 0.2 μm is deposited on the surface of the N functional layer; the deposition process parameters are:

[0122] The temperature is 450°C, the bias voltage is -60V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 16min;

[0123] S6. After the temperature drops to room temperature, take out the sample to obtain a composite coated tool.

[0124] Comparative Example 1

[0125] The difference from Example 1 is that

[0126] S4. Close Al 0.55 Ti 0.45 Target, turn on Nb 0.5 Al 0.5 Target, in Al 0.55 Ti 0.45 Nb is deposited on the surface of N transition layer 0.5 Al 0.5 N functional layer, thickness is 3.0μm; deposition process parameters are:

[0127] The temperature is 450°C, the bias voltage is -80V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 240min;

[0128] S5. Close Nb 0.5 Al 0.5 Target, open the Zr target, in Nb 0.5 Al 0.5 A ZrN coating with a thickness of 0.2 μm is deposited on the surface of the N functional layer; the deposition process parameters are:

[0129] The temperature is 450°C, the bias voltage is -60V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate is 1500sccm, and time is 16min.

[0130] Comparative Example 2

[0131] The difference from Example 1 is that

[0132] S4. Close Al 0.55 Ti 0.45 Target, turn on Nb 0.5 Al 0.46 B 0.04 Target, in Al 0.55 Ti 0.45 Nb is deposited on the surface of N transition layer0.5 Al 0.46 B 0.04 N functional layer, thickness is 3.0μm; deposition process parameters are:

[0133] The temperature is 450°C, the bias voltage is -80V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 240min;

[0134] S5. Close Nb 0.5 Al 0.46 B 0.04 Target, open the Zr target, in Nb 0.5 Al 0.46 B 0.04 A ZrN coating with a thickness of 0.2 μm is deposited on the surface of the N functional layer; the deposition process parameters are:

[0135] The temperature is 450°C, the bias voltage is -60V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate is 1500sccm, and time is 16min.

[0136] Comparative Example 3

[0137] The difference from Example 1 is that

[0138] S4. Close Al 0.55 Ti 0.45 Target, turn on Nb 0.5 Al 0.46 Si 0.04 Target, in Al 0.55 Ti 0.45 Nb is deposited on the surface of N transition layer 0.5 Al 0.46 Si 0.04 N functional layer, thickness is 3.0μm; deposition process parameters are:

[0139] The temperature is 450°C, the bias voltage is -80V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate of 1500sccm, time of 240min;

[0140] S5. Close Nb 0.5 Al 0.46 Si 0.04 Target, open the Zr target, in Nb 0.5 Al 0.46 Si 0.04 A ZrN coating with a thickness of 0.2 μm is deposited on the surface of the N functional layer; the deposition process parameters are:

[0141] The temperature is 450°C, the bias voltage is -60V, the arc current is 120A, and the gas pressure is 6.2×10 -2 mbar, N2 flow rate is 1500sccm, and time is 16min.

[0142] Comparative Example 4

[0143] The difference from Example 1 is that

[0144] Step S5 is not performed.

[0145] The performance of the composite coating cutting tools prepared in each embodiment and comparative example was tested, and the results are shown in Table 1.

[0146] Table 1

[0147]

[0148] It can be seen from Table 1 that the composite coating blade prepared in the embodiment of the present invention is higher in hardness, bonding strength and high-temperature oxidation resistance than the control example, indicating that adding a certain amount of B and Si in the NbAlN coating can not only enhance the hardness and oxidation resistance of the coating, but also reduce the appropriate coating friction coefficient value. In addition, the surface layer of ZrN can play an antioxidant role.

[0149] The cutting performance of the composite coating tool prepared by the embodiments and comparative examples of the present invention was tested as follows, wherein:

[0150] Test condition 1 is as follows:

[0151] Material: 316L stainless steel

[0152] Blade type: CNMG120408-MC3

[0153] Cutting conditions: cutting speed 140m / min, feed 0.2mm / z, cutting depth 1.5mm

[0154] The measurement results of the wear VB (unit: mm) of the insert flank after cutting for different times are shown in Table 2. The wear of the insert flank was measured using an OLYMPUS SZ61 optical super-depth microscope with a scale.

[0155] Table 2

[0156]

[0157] It can be seen from Table 2 ("--" in Table 2 represents that the tool has failed) that, under the same tool substrate and the same cutting conditions, the cutting performance of the composite coating tool of the present invention is better than that of the comparative example.

[0158] The composite coating tool prepared by the arc ion plating process comprises a cemented carbide tool substrate and a composite coating on the substrate. 1-x Ti x As an intermediate layer, the N coating has high bonding strength, thereby improving the Nb a Al b B c Si d The bonding strength between the N functional layer and the substrate; due to the Nb a Al b B c Si d a-Si3N4 and BN in the N coating work together to refine the grains, and a-Si3N4 and BN have excellent resistance to chemical diffusion; and ZrN serves as the surface layer, so the composite coated tool not only has high hardness and high bonding strength, but also has good oxidation resistance and anti-stickiness; and the preparation process of the composite coated tool is simple, easy to operate, and suitable for industrial production.

[0159] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A composite coated tool, It is characterized in that It includes a cemented carbide tool substrate and a composite coating on the substrate; The composite coating is prepared by a physical vapor deposition method, and includes, from the substrate to the outside, an M bonding layer, an MN transition layer deposited on the surface of the M bonding layer, an Al 1-x Ti x N intermediate layer, deposited on Al 1-x Ti x Nb on the surface of N intermediate layer a Al b B c Si d N functional layer, deposited on Nb a Al b B c Si d ZrN coating on the surface of N functional layer; Among them, 0.4≤x≤0.6, 0<a≤0.6, 0<b≤0.4, 0<c≤0.08, 0<d≤0.08, a+b+c+d=1; The M bonding layer is any one of a Nb bonding layer, a Zr bonding layer, and a Ta bonding layer; The MN transition layer is any one of a NbN transition layer, a ZrN transition layer and a TaN transition layer.

2. The composite coated tool according to claim 1, It is characterized in that The thickness of the M bonding layer is 0.05-0.1 μm.

3. The composite coated tool according to claim 1, It is characterized in that The thickness of the MN transition layer is 0.1-0.2 μm.

4. The composite coated tool according to claim 1, It is characterized in that The Al 1-x Ti x The thickness of the N intermediate layer is 0.1~0.5μm and the hardness is 22~26GPa.

5. The composite coated tool according to claim 1, It is characterized in that The Nb a Al b B c Si d The thickness of the N functional layer is 0.5~3.5μm, the hardness is 30~43GPa, and the friction coefficient is 0.3~0.

5.

6. The composite coated tool according to claim 1, It is characterized in that The ZrN coating has a thickness of 0.2-0.7 μm and a hardness of 20-30 GPa.

7. A method for preparing a composite coated tool according to any one of claims 1 to 6, It is characterized in that The composite coating is prepared by arc ion plating process, comprising the following steps: S1, depositing a bonding layer M on the substrate; S2, depositing a MN transition layer on the surface of the M bonding layer; S3. Deposition of Al on the surface of MN transition layer 1-x Ti x N intermediate layer; deposition process parameters are: The temperature is 400~550℃, the bias voltage is -80~-120V, the arc current is 100~130A, and the gas pressure is 5.0×10 -2 ~1.0×10 - 1 mbar, N 2 The flow rate is 1000~2500sccm and the time is 8~40min; S4. In Al 1-x Ti x Nb is deposited on the surface of N intermediate layer a Al b B c Si d N functional layer; deposition process parameters are: The temperature is 400~550℃, the bias voltage is -60~-120V, the arc current is 100~140A, and the gas pressure is 5.0×10 -2 ~1.0×10 - 1 mbar, N 2 The flow rate is 1000~2500sccm and the time is 40~280min; S5, in Nb a Al b B c Si d ZrN coating is deposited on the surface of N functional layer; the deposition process parameters are: The temperature is 400~550℃, the bias voltage is -40~-100V, the arc current is 100~140A, and the gas pressure is 5.0×10 -2 ~1.0×10 - 1 mbar, N 2 The flow rate is 1000~2500sccm and the time is 16~56min; S6. After the temperature drops to room temperature, take out the sample at room temperature to obtain a composite coating tool.

8. The method for preparing the composite coating tool according to claim 7, It is characterized in that Before step S1, the following steps are also included: S0. Pre-processing; The carbide tool is used as a substrate. After being sandblasted, cleaned and dried, the substrate is placed on a rotating rack, and the surface of the substrate is cleaned by glow discharge.

9. The method for preparing a composite coating tool according to claim 7, It is characterized in that In step S1, the specific process parameters for depositing the M bonding layer on the substrate are: The temperature is 400~550℃, the bias voltage is -120~-200V, the arc current is 100~140A, and the gas pressure is 0.8×10 -2 ~2.0×10 - 2 mbar, Ar flow rate is 1000~2000sccm, and time is 4~8min.

10. The method for preparing a composite coating tool according to claim 7, It is characterized in that In step S2, the specific process parameters for depositing the MN transition layer on the surface of the M bonding layer are: The temperature is 400~550℃, the bias voltage is -80~-150V, the arc current is 100~140A, and the gas pressure is 5.0×10 -2 ~1.0×10 - 1 mbar, N 2 The flow rate is 1000~2500sccm and the time is 8~16min.

Citation Information

Patent Citations

  • Cemented carbide cutting tool for multi-component coating

    CN101407905A

  • Surface coated cutting tool

    JP2011189435A